PERSEPSI SISWA TUNARUNGU TERHADAP PENGGUNAAN SISTEM ISYARAT BAHASA INDONESIA DALAM KOMUNIKASI (Penelitian Deskriptif Kuantitatif di SLB se-Kota Padang) - Angga Nikola Fortuna (Jurnal Penelitian Pendidikan Khusus, 2014)
Abstrak : This is a background research exploring the perceptions of deaf students in Padang citywho use Indonesian Sign Language System (SIBI) for communicating. The methodology used in the research is both quantitative and descriptive and the data has been analysed as a percentage. The results indicate that the perception of deaf students using SistemIsyarat Bahasa Indonesia to communicate in Special Development Schools (SLB) in Padang is high in several aspects. Key words : Perception; deaf; SIBI